The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7554/elife.55294
|View full text |Cite
|
Sign up to set email alerts
|

Different methods of fear reduction are supported by distinct cortical substrates

Abstract: Understanding how learned fear can be reduced is at the heart of treatments for anxiety disorders. Tremendous progress has been made in this regard through extinction training in which the aversive outcome is omitted. However, current progress almost entirely rests on this single paradigm, resulting in a very specialized knowledgebase at the behavioural and neural level of analysis. Here, we used a dual-paradigm approach to show that different methods that lead to reduction in learned fear in rats are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…The observation of impaired Pavlovian acquisition is consistent with reports of impaired extinction in reversal learning tasks (Izquierdo, 2017), and simple Pavlovian extinction procedures (Lay et al, 2020;Panayi & Killcross, 2014;Zimmermann et al, 2018) following OFC dysfunction. We have previously shown that OFC inactivation disrupts extinction learning over multiple sessions, however, within each extinction session OFC inactivation did not prevent extinction behavior (i.e., decreasing responding).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The observation of impaired Pavlovian acquisition is consistent with reports of impaired extinction in reversal learning tasks (Izquierdo, 2017), and simple Pavlovian extinction procedures (Lay et al, 2020;Panayi & Killcross, 2014;Zimmermann et al, 2018) following OFC dysfunction. We have previously shown that OFC inactivation disrupts extinction learning over multiple sessions, however, within each extinction session OFC inactivation did not prevent extinction behavior (i.e., decreasing responding).…”
Section: Resultssupporting
confidence: 88%
“…presented in extinction. Again, OFC dysfunction results in persistent responding to A-in extinction (Butter, 1969;Lay et al, 2020;Panayi & Killcross, 2014).…”
Section: Reversal Learningmentioning
confidence: 99%
“…The current findings align with and extend prior work implicating the mPFC and BNST in various situations in which there is ambiguity and uncertainty about a threat. For example, the mPFC is engaged in settings that require integration of higher-order cues to gate learned responses ( Halladay and Blair, 2015 ; Halladay and Blair, 2017 ; Sharpe and Killcross, 2018 ; Marek et al, 2019 ), or where there is conflict between excitatory and inhibitory CS associations, for instance in fear extinction ( Milad and Quirk, 2012 ; Bloodgood et al, 2018 ; Lay et al, 2020 ), fear discrimination ( Grosso et al, 2018 ), threat/safety conditioning ( Sangha et al, 2014 ; Meyer et al, 2019 ), and punished reward-seeking ( Burgos-Robles et al, 2017 ; Halladay et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Learned inhibition is a function attributed to the mPFC and in particular the IL. For example, pharmacological, optogenetic, and chemogenetic inhibition of the IL impairs the formation and/or retrieval of fear extinction memories ( Laurent and Westbrook, 2009 ; Bukalo et al, 2015 ; Do-Monte et al, 2015 ; Kim et al, 2016 ; Lay et al, 2020 ; Bukalo et al, 2021 ) and the expression of learned safety acquired through explicit CS–US unpairing ( Sangha et al, 2014 ). Conversely, presentation of a safety signal during inescapable stress decreases activity (c-Fos) in a lateral area of BNST encompassing avBNST ( Christianson et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is evidence for multiple types of extinction, which may be largely dependent on the protocol employed (Goodman & Packard, 2019). Recent evidence has further demonstrated that extinction based on omission relies on the infralimbic cortex whereas extinction based on overexpectation employs the orbitofrontal cortex (Lay et al, 2020).…”
Section: Discussionmentioning
confidence: 99%